1998
DOI: 10.1055/s-1998-2125
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Cα,α-Disubstituted (Diarylaminomethyl)-phosphonates

Abstract: A convenient and efficient three-step procedure for the preparation of N -protected or unprotected C α,α -disubstituted (diarylaminomethyl)phosphonates 1 is reported. This method allows diversification of the substituents on the carbon in the α -position to the phosphorus, as well as the protective group on the amine and the phosphonate ester group.Over the past three decades, several research projects have been directed toward the synthesis of α -aminophosphonic acids 2 and their esters, analogs of amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…This study of activating groups on the nitrogen atom revealed that sulfonyl‐ or TcBoc‐activated imines provided the best combination of yield, enantioselectivity, and diastereoselectivity to date in a practical, user‐friendly catalytic process 10. These groups were therefore tested with a range of imines derived from aromatic, heteroaromatic, unsaturated, and even aliphatic aldehydes and ketones11 (Table 2). As sulfonyl‐substituted imines were easier to prepare than TcBoc‐substituted ones, most studies were conducted with the former group.…”
Section: Effect Of the Nitrogen Substituent On The Yield Diastereosementioning
confidence: 99%
“…This study of activating groups on the nitrogen atom revealed that sulfonyl‐ or TcBoc‐activated imines provided the best combination of yield, enantioselectivity, and diastereoselectivity to date in a practical, user‐friendly catalytic process 10. These groups were therefore tested with a range of imines derived from aromatic, heteroaromatic, unsaturated, and even aliphatic aldehydes and ketones11 (Table 2). As sulfonyl‐substituted imines were easier to prepare than TcBoc‐substituted ones, most studies were conducted with the former group.…”
Section: Effect Of the Nitrogen Substituent On The Yield Diastereosementioning
confidence: 99%
“…The aldimines ( p -tol)CHN(C 6 H 4 - p -CO 2 Me) ( 3a-Tol ), (Ph)CHN(C 6 H 4 - p -CO 2 Me) ( 3a-Ph ), (Ph)CHNPh ( 3b ), and ( p -tol)CHN(C 6 H 4 - p -OMe) ( 3c ) were prepared using procedures reported for the preparation of similar compounds . [(DPPE)Rh(μ-Cl)] 2 , 4-methylbenzophenone imine, 4,4‘-dimethylbenzophenone imine, solid p -tolyllithium, 20b , 21b , and 25 129 were prepared according to literature procedures. Compound 18b 130 was synthesized by PCC oxidation of 20b in CH 2 Cl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A solution of triethylamine (0.01 mol) in diethyl ether (20 ml) was added to a stirred solution of freshly prepared benzeneoximoyl chloride, obtained from 0.01 mol of a-benzaldoxime (Baruah et al, 1988) and dissolved in diethyl ether (50 ml) at a temperature below 273 K. This was followed by the addition of a benzophenone imine (0.01 mol) (Cristau et al, 1998) solution in diethyl ether (30 ml). The resulting mixture was stirred for 24 h without cooling, extracted with water (30 ml), 15% hydrochloric acid (3 x 30 ml), and again with water.…”
Section: Methodsmentioning
confidence: 99%